Positive electrode active material, and positive electrode and lithium secondary battery comprising the same
Patent Information
- Application Number
- KR1020250030625
- Authority / Receiving Office
- KR · KR
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-10
- Publication Date
- 2026-09-17
Smart Images

Figure PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a positive electrode active material, and a positive electrode and a lithium secondary battery comprising the same. Background Technology
[0003] With the increasing technological development and demand for mobile devices, the demand for rechargeable batteries as an energy source is rapidly rising. Among these rechargeable batteries, lithium-ion batteries, which possess high energy density and voltage, long cycle life, and low self-discharge rates, have been commercialized and are widely used.
[0004] Lithium composite transition metal oxides are used as cathode active materials for lithium secondary batteries; among these, lithium cobalt composite metal oxides such as LiCoO2 are primarily used due to their high operating voltage and excellent capacity characteristics. However, LiCoO2 has very poor thermal properties due to the instability of its crystal structure caused by lithium delithiation, and because it is expensive, there are limitations to its mass use as a power source in fields such as electric vehicles.
[0005] As materials to replace LiCoO2, lithium manganese composite metal oxides (LiMnO2 or LiMn2O4, etc.), lithium iron phosphate compounds (LiFePO4, etc.), or lithium nickel composite metal oxides (LiNiO2, etc.) have been developed. Among these, research and development on lithium nickel composite metal oxides is being conducted more actively, as they have a high reversible capacity of about 200 mAh / g, making it easy to implement large-capacity batteries. However, LiNiO2 has poor thermal stability compared to LiCoO2, and there is a problem in that if an internal short circuit occurs due to external pressure or other factors while charged, the positive active material itself decomposes, leading to the rupture and ignition of the battery.
[0006] Accordingly, as a method to improve the low thermal stability of LiNiO2 while maintaining its excellent reversible capacity, nickel-cobalt-manganese-based lithium composite transition metal oxides in which part of Ni is substituted with Mn and Co, and nickel-manganese-aluminum-based lithium composite transition metal oxides in which part of Ni is substituted with Mn and Al have been developed.
[0007] However, the rising price of cobalt raw materials included in lithium composite transition metal oxides has also emerged as a significant issue, and as the price of the aforementioned cobalt raw materials is expected to continue increasing, a cathode active material with reduced cobalt content has been developed accordingly.
[0008] Conventional lithium composite transition metal oxides were generally in the form of spherical secondary particles formed by the aggregation of tens to hundreds of primary particles. However, in the case of lithium composite transition metal oxides in the form of secondary particles with many primary particles aggregated in this manner, particle breakage is prone to occur during the rolling process when primary particles detach during cathode manufacturing. Furthermore, when the battery is operated at high voltage to compensate for energy density and capacity, there is a problem that cracks occur inside the particles during the charging and discharging process. If particle breakage or cracking occurs in the cathode active material, the contact area with the electrolyte increases, leading to increased gas generation and degradation of the cathode active material due to side reactions with the electrolyte.
[0009] Meanwhile, in the case of lithium composite transition metal oxides in which the nickel content among the total metals excluding lithium is 50 mol% or more, structural and chemical stability are further reduced, thermal stability is more difficult to secure, and there are also cost issues due to high heat treatment temperatures.
[0010] Therefore, there is a need to develop high-nickel cathode active materials capable of realizing lithium secondary batteries with improved capacity and lifespan characteristics. The problem to be solved
[0012] The present invention aims to solve the above-mentioned problems by providing a positive electrode active material capable of improving the lifespan characteristics while improving the charge / discharge capacity, efficiency, and resistance characteristics of a battery.
[0013] In addition, the present invention aims to provide a positive electrode and a lithium secondary battery having excellent lifespan characteristics, resistance characteristics, and capacity characteristics, including the positive electrode active material as described above. means of solving the problem
[0015] (1) The present invention provides a positive electrode active material comprising a lithium composite transition metal oxide in the form of a single particle consisting of 50 or fewer primary particles, and having a unit uniformity of 3.5% or more and 10.0% or less according to Formula 1 below.
[0016] [Equation 1]
[0017] Unit Uniformity = (PDI × Derivative × Span)
[0018] In the above Equation 1,
[0019] PDI is Dv A / Dn A And,
[0020] The fraction is the volume percentage [unit: %] of primary particles with a particle size of 1 μm or less among the particle sizes of primary particles obtained from SEM images, and
[0021] Span is (Dv 90 -Dv 10 ) / Dv 50 And,
[0022] The above Dv A is the particle diameter of the primary particle [unit: μm] corresponding to the arithmetic mean of the volume of the primary particle obtained from the SEM image, and
[0023] The above Dn A is the primary particle diameter [unit: μm] corresponding to the arithmetic mean of the primary particle diameters obtained from the SEM image, and
[0024] The above Dv n Is It is the particle size of the primary particle corresponding to n% of the volume cumulative distribution of the primary particle obtained from the SEM image [unit: μm].
[0025] (2) The present invention provides a positive electrode active material according to (1), wherein the lithium composite transition metal oxide has a nickel (Ni) content of 50 mol% or more among the total metals excluding lithium.
[0026] (3) The present invention provides a positive electrode active material in which, in (1) or (2), the lithium composite transition metal oxide has a composition represented by the following chemical formula 1.
[0027] [Chemical Formula 1]
[0028] Li 1+x Ni a Co b Mn c M 1 d O2
[0029] In the above chemical formula 1,
[0030] M 1 It is one or more selected from the group consisting of Al, Y, Zr, K, Sr, Ba, B, Ce, Cr, Mg, V, Ti, Fe, Zn, Si, Nb, Ga, Sn, Mo, W, and P, and
[0031] -0.1≤x≤0.3, 0.500≤a<1.000, 0.000 <b<0.500, 0.000<c<0.500, 0.000≤d≤0.100이다.
[0032] (4) The present invention provides a positive electrode active material in any one of (1) to (3), wherein the PDI is 1.50 or higher and 1.90 or lower.
[0033] (5) The present invention, in any one of (1) to (4), wherein Dn A The present invention provides a positive electrode active material having a thickness of 1.50 μm or more and 2.00 μm or less.
[0034] (6) The present invention, in any one of (1) to (5), wherein the Dv A The present invention provides a positive electrode active material having a thickness of 3.00 μm or more and 3.30 μm or less.
[0035] (7) The present invention, in any one of (1) to (6), Dv 50 The provides a positive electrode active material having a thickness of 2.50 μm or more and 3.00 μm or less.
[0036] (8) The present invention provides a positive electrode active material in any one of (1) to (7), wherein the span is 0.50 or more and 0.95 or less.
[0037] (9) The present invention provides a positive electrode active material in which, in any one of (1) to (8), the differential fraction is 2.5% or more and 5.0% or less.
[0038] (10) The present invention provides a positive electrode active material in which, in any one of (1) to (9), the unit uniformity is 3.8% or more and 7.5% or less.
[0039] (11) In any one of (1) to (10) above, the present invention is an average particle size (D) measured by a particle size analyzer (PSA). 50 ) provides a positive electrode active material having a thickness of 3.00 μm or more and 5.00 μm or less.
[0040] (12) The present invention provides a positive electrode comprising a positive electrode active material according to any one of (1) to (11).
[0041] (13) The present invention provides a lithium secondary battery comprising a positive electrode according to (12) above. Effects of the invention
[0043] The positive electrode active material according to the present invention controls the particle size of the primary particles, specifically by satisfying the unit uniformity according to Formula 1 described in this specification within a specific range, thereby controlling the interface of the primary particles that serves as a pathway for lithium ions, and has the effect of securing an optimal pathway during the extraction and insertion of lithium ions. Accordingly, the charge / discharge capacity, efficiency, initial resistance, and lifespan characteristics of a battery containing the positive electrode active material are improved.
[0044] Accordingly, the lifespan characteristics, efficiency characteristics, capacity characteristics, and resistance characteristics of the anode and secondary battery containing the above-mentioned anode active material are improved. Brief explanation of the drawing
[0046] Figure 1 is an SEM image (approx. 5K magnification) of the cathode active material prepared in Example 1. Figure 2 is an SEM image (approx. 5K magnification) of the positive electrode active material prepared in Example 2. Figure 3 is an SEM image (approx. 5K magnification) of the cathode active material prepared in Comparative Example 1. Figure 4 is an SEM image (approx. 5K magnification) of the cathode active material prepared in Comparative Example 2. Figure 5 is an SEM image (approx. 5K magnification) of the cathode active material prepared in Comparative Example 3. Specific details for implementing the invention
[0047] Hereinafter, the present invention will be described in more detail to aid in understanding the invention.
[0048] Terms and words used in this specification and claims shall not be interpreted as being limited to their ordinary or dictionary meanings, but shall be interpreted in a meaning and concept consistent with the technical spirit of the invention, based on the principle that the inventor can appropriately define the concept of the terms to best describe his invention.
[0049] In this specification, terms such as 'comprising,' 'having,' or 'having' are intended to specify the existence of the implemented features, numbers, steps, components, or combinations thereof, and should not be understood as precluding the existence or addition of one or more other features, numbers, steps, components, or combinations thereof.
[0050] In this specification, 'primary particle' refers to the smallest unit of a particle recognized when observing the positive active material using a scanning electron microscope (SEM), and 'secondary particle' refers to a secondary structure formed by the aggregation of multiple primary particles.
[0051] In this specification, the term 'single particle form' refers to a form composed of 50 or fewer primary particles, as opposed to a spherical secondary particle form formed by the aggregation of tens to hundreds of primary particles manufactured by conventional methods. Specifically, in the present invention, the single particle form may be a single particle composed of one primary particle, or a secondary particle form formed by the aggregation of 2 to 50 primary particles.
[0052] In this specification, the particle size corresponding to each of the n primary particles (an average of 10,000 or more primary particles) present in the SEM image can be verified by processing the scanning electron microscope (SEM) image with an image processing program (LG Chem, DX program). Specifically, it can be measured from a two-dimensional segmentation image partitioned by primary particle units obtained by image processing using an artificial intelligence model. The segmentation image can be obtained by acquiring a scanning electron microscope (SEM) image of the cathode active material powder to be measured, inputting the acquired scanning electron microscope image into a U-NET structure or the like to generate a boundary image, removing the boundaries from the scanning electron microscope (SEM) image based on the boundary image to generate a boundary removal image, identifying multiple objects included in the boundary removal image, and then segmenting the SEM image into primary particle units based on the multiple objects.
[0053] In this specification, the particle size of a primary particle may be calculated by calculating the area of each primary particle through the number of pixels corresponding to each of the n primary particles present in the segmentation image, and by using the radius of a circle having the same area as the area of each primary particle to calculate the particle size of each primary particle present in the segmentation image.
[0054] In this specification, the volume of a primary particle may be calculated by calculating the area of each primary particle through the number of pixels corresponding to each of the n primary particles present in the segmentation image, and by defining the volume of a sphere having the radius of a circle having the same area as the area of each primary particle as the volume of each primary particle present in the segmentation image.
[0055] In this specification, the differential is a primary particle with a particle diameter of 1 μm or less, calculated by calculating the area of each primary particle through the number of pixels corresponding to each of the n primary particles present in the SEM image and calculating the particle diameter of each primary particle present in the SEM image using the radius of a circle having the same area as the area of each primary particle.
[0056] In this specification, 'average particle size' can be defined as the particle size corresponding to 50% of the volume cumulative distribution in the particle size distribution curve (graph curve of the particle size distribution). The average particle size can be measured by dispersing the powder to be measured in a dispersion medium, introducing it into a commercially available laser diffraction particle size measuring device (Microtrac, S3500), calculating the particle size distribution by measuring the difference in diffraction patterns according to particle size as the particles pass through a laser beam, and calculating the particle diameter at the point where the volume cumulative distribution according to particle size in the measuring device is 50%.
[0058] positive electrode active material
[0059] Hereinafter, the positive active material according to the present invention will be described.
[0061] The positive electrode active material according to the present invention comprises a lithium composite transition metal oxide in the form of a single particle composed of 50 or fewer primary particles, and has a unit uniformity according to Formula 1 below of 3.5% or more and 10.0% or less.
[0062] [Equation 1]
[0063] Unit Uniformity = (PDI × Derivative × Span)
[0064] PDI is Dv A / Dn A and, the differential fraction is the volume percentage [unit: %] of primary particles with a particle size of 1 μm or less among the particle sizes of primary particles obtained from the SEM image, and the span is (Dv 90 -Dv 10 ) / Dv 50 and, the above DvA is the particle diameter of the primary particle [unit: μm] corresponding to the arithmetic mean of the volume of the primary particle obtained from the SEM image, and the above Dn A is the particle size of the primary particle corresponding to the arithmetic mean of the particle sizes of the primary particles obtained from the SEM image [unit: μm], and the above Dv n Is It is the particle size of the primary particle corresponding to n% of the volume cumulative distribution of the primary particle obtained from the SEM image [unit: μm].
[0065] The above lithium composite transition metal oxide is in the form of a single particle composed of 50 or fewer primary particles. That is, the above lithium composite transition metal oxide is in the form of a single particle or a single particle formed by the aggregation of two or more and 50 or fewer primary particles. The above single particle form is distinguished from a secondary particle formed by the aggregation of more than 50 primary particles. When the above lithium composite transition metal oxide has a single particle form, it has excellent stability, so even when the positive active material containing it is rolled, the positive active material does not break or crack, and side reactions between the positive active material and the electrolyte can be reduced. As a result, durability against volume change during charging and discharging of the battery is improved, and lifespan characteristics can be improved. When the above lithium composite transition metal oxide is in the form of a secondary particle, the positive active material containing it breaks or cracks, and there is a problem of inferior lifespan characteristics due to side reactions between the positive active material and the electrolyte.
[0066] In the present invention, unit uniformity is evaluated and represented by a parameter indicated by Equation 1 described in this specification. The unit uniformity referred to in the present invention is a value controlled according to the particle size of the primary particles constituting the single particle, and a smaller unit uniformity value indicates that the primary particles have a uniform particle size. That is, the closer the unit uniformity is to 0, the more evenly the particle sizes of the primary particles are distributed and the smaller the particle size variation.
[0067] The unit uniformity described in the present invention appears smaller as the PDI, fineness ratio, and span described in this specification become smaller. The PDI is the value of the primary particle diameter corresponding to the arithmetic mean of the primary particle diameter obtained from the SEM image and the primary particle diameter corresponding to the arithmetic mean of the primary particle diameter obtained from the SEM image; the closer the PDI is to 1, the more similar the primary particle diameter corresponding to the arithmetic mean of the primary particle diameter and the primary particle diameter corresponding to the arithmetic mean of the primary particle volume are, and the size of the primary particle is uniform. The smaller the fineness ratio, the smaller the fineness content of the primary particle in the cathode active material, and the smaller the span, the more uniform the particle size distribution of the primary particle in the cathode active material.
[0068] Meanwhile, the unit uniformity may be 3.5% or more, 3.6% or more, 3.7% or more, or 3.8% or more, and may be 7.5% or less, 8.0% or less, 8.5% or less, 9.0% or less, 9.5% or less, or 10.0% or less. When the unit uniformity is within the above range, it has the effect of improving lifespan characteristics while maintaining the capacity, efficiency, and resistance characteristics of the electrode or battery.
[0070] According to one embodiment of the present invention, the lithium composite transition metal oxide may have a nickel (Ni) content of 50 mol% or more among the total metals excluding lithium. Specifically, the lithium composite transition metal oxide may have a nickel (Ni) content of 50 mol% or more, 55 mol% or more, or 60 mol% or more among the transition metals excluding lithium, or 65 mol% or less, 70 mol% or less, 75 mol% or less, 80 mol% or less, 85 mol% or less, 90 mol% or less, 95 mol% or less, or less than 100 mol%. When the nickel (Ni) content is within the above range, the capacity characteristics of the cathode active material can be improved. Specifically, when the nickel (Ni) content is 55 mol% or more and 65 mol% or less, the capacity characteristics can be improved while maintaining the lifespan characteristics.
[0072] According to one embodiment of the present invention, the lithium composite transition metal oxide may have a composition represented by the following chemical formula 1.
[0073] [Chemical Formula 1]
[0074] Li 1+x Ni a Co b Mn c M 1 d O2
[0075] In the above chemical formula 1,
[0076] M 1 It is one or more selected from the group consisting of Al, Y, Zr, K, Sr, Ba, B, Ce, Cr, Mg, V, Ti, Fe, Zn, Si, Nb, Ga, Sn, Mo, W, and P, and
[0077] -0.1≤x≤0.3, 0.500≤a<1.000, 0.000 <b<0.500, 0.000<c<0.500, 0.000≤d≤0.100이다.
[0078] The above M 1 is a doping element, specifically the above M 1 ... may be one or more selected from the group consisting of Al, Y, Zr, K, Sr, Ba, B, Ce, Cr, F, Mg, V, Ti, Fe, Zn, Si, Nb, Ga, Sn, Mo, W, and P. The above M 1 Although it is not necessarily included, if included in an appropriate amount, the particle shape of the positive active material can be improved and the stability of the crystal structure can be enhanced.
[0079] Meanwhile, the above x may be -0.1 or greater, -0.05 or greater, or 0.0 or greater, and may be 0.05 or less, 0.1 or less, 0.15 or less, 0.2 or less, 0.25 or less, or 0.3 or less. When x satisfies the above range, high capacity characteristics and high energy density per unit volume can be realized.
[0080] The above a is the mole fraction of nickel (Ni) among all metals excluding lithium in the lithium composite transition metal oxide, and may be 0.500 or more, 0.550 or more, or 0.600 or more, and may be 0.650 or less, 0.700 or less, 0.750 or less, 0.800 or less, 0.850 or less, 0.900 or less, 0.950 or less, or less than 1.000. When a is within the above range, the capacity characteristics of the cathode active material can be improved. In particular, when a is 0.55 or more and 0.65 or less, price competitiveness is excellent, and the structural stability and thermal stability of the cathode active material can be improved.
[0081] The above b is the mole fraction of cobalt (Co) among all metals excluding lithium in the lithium composite transition metal oxide, and may be greater than 0.000, greater than or equal to 0.005, or greater than or equal to 0.100, and less than or equal to 0.150, less than or equal to 0.200, less than or equal to 0.250, less than or equal to 0.300, less than or equal to 0.350, less than or equal to 0.400, less than or equal to 0.450, or less than or equal to 0.500. When b satisfies the above range, it has the effect of improving capacitance characteristics without degrading lifespan characteristics and resistance characteristics.
[0082] The above c is the mole fraction of manganese (Mn) among the total metals excluding lithium in the lithium complex transition metal oxide, It may be greater than 0.000, greater than or equal to 0.005, greater than or equal to 0.100, greater than or equal to 0.150, greater than or equal to 0.200, or greater than or equal to 0.250, and may be less than or equal to 0.300, less than or equal to 0.350, less than or equal to 0.400, less than or equal to 0.450, or less than or equal to 0.500. When c satisfies the above range, structural stability increases and the decomposition reaction of the electrolyte may be relatively reduced.
[0083] The above d is M among the total metals excluding lithium in the lithium complex transition metal oxide. 1The mole fraction of c may be 0.000 or more, 0.001 or more, 0.002 or more, or 0.003 or more, and may be 0.004 or less, 0.005 or less, 0.006 or less, 0.007 or less, 0.008 or less, 0.009 or less, 0.010 or less, 0.020 or less, 0.030 or less, 0.040 or less, 0.050 or less, 0.060 or less, 0.070 or less, 0.080 or less, 0.090 or less, or 0.100 or less. When c satisfies the above range, the stability of the crystal structure of the positive active material can be improved and the particle shape can be improved.
[0084] The above a, b, c, and d may be a+b+c+d=1.000.
[0086] According to one embodiment of the present invention, the PDI may be 1.50 or higher and 1.90 or lower. Specifically, the PDI may be 1.50 or higher, 1.60 or higher, or 1.70 or higher, and may be 1.87 or lower, 1.88 or lower, 1.89 or lower, or 1.90 or lower. When the PDI is within the above range, the primary particles grow to an appropriate degree, thereby having the effect of improving lifespan characteristics while maintaining the capacity, efficiency, and resistance characteristics of the electrode or battery.
[0088] According to one embodiment of the present invention, the Dn A may be 1.50 μm or more and 2.00 μm or less. Specifically, the above Dn A may be 1.50 μm or more, 1.55 μm or more, or 1.60 μm or more, and may be 1.85 μm or less, 1.90 μm or less, 1.95 μm or less, or 2.00 μm or less. The above Dn A If it is within the above range, improving lithium mobility has the effect of improving capacity characteristics and lifespan characteristics.
[0090] According to one embodiment of the present invention, the Dv Amay be 3.00 μm or more and 3.30 μm or less. Specifically, the above Dv A may be 3.00 μm or more, or 3.15 μm or less, 3.20 μm or less, 3.25 μm or less, or 3.30 μm or less. The above Dv A If it is within the above range, improving lithium mobility has the effect of improving capacity characteristics and lifespan characteristics.
[0092] According to one embodiment of the present invention, the Dv 50 may be 2.50 μm or more and 3.00 μm or less. Specifically, the above Dv 50 may be 2.50 μm or more, 2.90 μm or less, or 3.00 μm or less. The above Dv 50 If it is within the above range, improving lithium mobility has the effect of improving capacity characteristics and lifespan characteristics.
[0094] According to one embodiment of the present invention, the span may be 0.50 or more and 0.95 or less. Specifically, the span may be 0.50 or more, 0.60 or more, or 0.70 or more, and 0.95 or less. When the span is within the above range, the particle size distribution is uniform, and there is an effect of improving lifespan characteristics while maintaining the capacity, efficiency, and resistance characteristics of the electrode or battery.
[0096] According to one embodiment of the present invention, the differential fraction may be 2.5% or more and 5.0% or less. Specifically, the differential fraction may be 2.5% or more, 2.6% or more, 2.7% or more, or 2.8% or more, and may be 4.5% or less, 4.6% or less, 4.7% or less, 4.8% or less, 4.9% or less, or 5.0% or less. When the differential fraction is within the above range, there is an effect of improving lifespan characteristics while maintaining the capacity, efficiency, and resistance characteristics of the electrode or battery.
[0098] According to one embodiment of the present invention, the positive active material has an average particle size (D) measured by a particle size analyzer (PSA). 50 ) may be 3.00 μm or more and 5.00 μm or less. Specifically, the above average particle size (D 50 ) may be 3.00 μm or more, 3.10 μm or more, 3.20 μm or more, 3.30 μm or more, 3.40 μm or more, 3.50 μm or more, 3.60 μm or more, 3.70 μm or more, or 3.80 μm or more, and may be 4.00 μm or less, 4.50 μm or less, or 5.00 μm or less. The above D 50 If it is within the above range, it has the effect of improving the capacity and lifespan characteristics of the electrode or battery.
[0100] The positive electrode active material of the present invention can be manufactured according to conventional methods in the art. Specifically, it can be manufactured by calcining a complex transition metal hydroxide and a lithium-containing raw material.
[0101] Specifically, the positive electrode active material of the present invention can be manufactured by a method for manufacturing a positive electrode active material comprising: (A) a step of preparing a mixture by mixing a complex transition metal hydroxide containing nickel, manganese, and cobalt with a lithium-containing raw material; and (B) a step of preparing a lithium complex transition metal oxide by calcining the mixture.
[0102] According to one embodiment of the present invention, in step (A), a complex transition metal hydroxide containing nickel and manganese, a lithium (Li)-containing raw material, and a doping element-containing raw material may be mixed in an amount such that they have a composition represented by Formula 1 as described in this specification.
[0103] The above lithium-containing raw material may be a lithium-containing sulfate, nitrate, acetate, carbonate, oxalate, citrate, halide, hydroxide, or oxyhydroxide, and is not particularly limited as long as it is soluble in water. Specifically, the above lithium-containing raw material may be Li2CO3, LiNO3, LiNO2, LiOH, LiOH·H2O, LiH, LiF, LiCl, LiBr, LiI, CH3COOLi, Li2O, Li2SO4, CH3COOLi, or Li3C6H5O7, and any one or more of these may be used.
[0104] The above composite transition metal hydroxide can be mixed such that the ratio (Li / M'') of the number of moles of lithium (Li) contained in the lithium-containing raw material to the total number of moles of transition metal (M'') contained in the composite transition metal hydroxide is 1.0 or higher, and 1.07 or lower, 1.08 or lower, 1.09 or lower, and 1.10 or lower.
[0105] When preparing the mixture of step (A) above, raw materials containing doping elements, such as aluminum-containing raw materials, zirconium-containing raw materials, or yttrium-containing raw materials, may be further mixed.
[0106] The above step (B) may be a multi-stage sintering process in which the mixture is sintered at a temperature of 960°C or higher and 990°C or lower to produce a sintered product, and then sintered at a temperature of 955°C or higher and 960°C or lower to produce a lithium composite transition metal oxide.
[0107] The above first firing may be performed under an atmospheric or oxygen atmosphere.
[0108] The above first firing may include a section of increasing the temperature from room temperature to the first firing temperature at a rate of 4°C / min or more and 6°C / min or less, and a section of decreasing the temperature from the first firing temperature to a temperature of 100°C or more and 150°C or less.
[0109] The above secondary firing may be performed under an atmospheric or oxygen atmosphere.
[0110] The above secondary firing may include a section in which the temperature is increased at a rate of 2°C / min or more and 5°C / min or less from a temperature of 100°C or more and 150°C or less to the secondary firing temperature.
[0111] The above secondary firing may be performed for a shorter period of time than the primary firing.
[0112] The positive active material manufactured according to the above method for manufacturing a positive active material may have a composition represented by Chemical Formula 1 described in this specification and may be in the form of a single particle. In addition, the positive active material manufactured according to the above method for manufacturing a positive active material may have a PDI of 1.50 or more and 1.90 or less as described in this specification, a fine fraction of 2.5% or more and 5.0% or less as described in this specification, a span of 0.50 or more and 0.95 or less as described in this specification, and a unit uniformity of 3.5% or more and 10.0% or less as described in this specification.
[0114] anode
[0115] Next, the anode according to the present invention will be described.
[0116] The anode according to the present invention comprises an anode active material layer comprising an anode active material according to the present invention. Specifically, the anode comprises an anode current collector and an anode active material layer formed on the anode current collector and comprising the anode active material. Since the anode material has been described above, a detailed explanation is omitted, and only the remaining components are described in detail below.
[0118] The above positive current collector is not particularly limited as long as it is conductive without causing chemical changes in the battery, and for example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface treated with carbon, nickel, titanium, silver, etc. may be used. In addition, the above positive current collector may typically have a thickness of 3 μm to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesion of the positive active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0120] The above-mentioned positive active material layer may include a conductive material and a binder together with the positive material. In this case, the positive material may be included in an amount of 80% to 99% by weight, more specifically 85% to 98.5% by weight, based on the total weight of the positive active material layer, and may exhibit excellent capacity characteristics within this range.
[0122] The above conductive material is used to impart conductivity to the electrode, and in the battery being constructed, it may be used without special limitations as long as it possesses electronic conductivity without causing chemical changes. Specific examples include graphite such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber such as copper, nickel, aluminum, or silver; conductive whiskers such as zinc oxide or potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and one of these alone or a mixture of two or more may be used. The above conductive material may be included in an amount of 0.1% to 15% by weight relative to the total weight of the positive electrode active material layer.
[0124] The above binder serves to improve adhesion between positive active material particles and adhesion between the positive material and the current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethylcellulose (CMC), starch, hydroxypropylcellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene butadiene rubber (SBR), fluororubber, or various copolymers thereof, and one of these alone or a mixture of two or more may be used. The above binder may be included in an amount of 0.1% to 15% by weight based on the total weight of the positive active material layer.
[0126] The above-described anode may be manufactured according to a conventional anode manufacturing method, except for using the anode material described above. Specifically, it may be manufactured by applying a composition for forming an anode active material layer, prepared by dissolving or dispersing the above-described anode material and, optionally, a binder and a conductive material in a solvent, onto an anode current collector, followed by drying and rolling. At this time, the types and contents of the anode material, binder, and conductive material are as described above. Alternatively, the above-described anode may be manufactured by casting the composition for forming an anode active material layer onto a separate support, and then laminating the film obtained by peeling from the support onto an anode current collector.
[0128] The above solvent may be a solvent commonly used in the relevant technical field, and may include dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and one of these alone or a mixture of two or more may be used. The amount of the above solvent used is sufficient if it has a viscosity that dissolves or disperses the anode active material, conductive material, and binder, taking into account the coating thickness of the slurry and the manufacturing yield, and subsequently provides excellent thickness uniformity when coated for anode manufacturing.
[0130] lithium secondary battery
[0131] Next, a lithium secondary battery according to the present invention will be described.
[0133] The present invention can manufacture an electrochemical device comprising the anode. Specifically, the electrochemical device may be a battery, a capacitor, etc., and more specifically, a lithium secondary battery.
[0135] Specifically, the above lithium secondary battery comprises a positive electrode, a negative electrode positioned opposite the positive electrode, and a separator and an electrolyte interposed between the positive electrode and the negative electrode. Since the positive electrode is identical to the one described above, a detailed description is omitted, and only the remaining components are described in detail below.
[0137] In addition, the lithium secondary battery may optionally further include a battery container that accommodates the electrode assembly of the positive electrode, negative electrode, and separator, and a sealing member that seals the battery container.
[0139] In the above lithium secondary battery, the negative electrode comprises a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.
[0140] The above-mentioned negative current collector is not particularly limited as long as it has high conductivity without causing chemical changes in the battery, and for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., and aluminum-cadmium alloy may be used. In addition, the above-mentioned negative current collector may typically have a thickness of 3 μm to 500 μm, and, similar to the positive current collector, fine irregularities may be formed on the surface of the current collector to strengthen the bonding strength of the negative active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0142] The above-mentioned cathode active material layer optionally includes a binder and a conductive material together with the cathode active material.
[0144] As the above-mentioned negative electrode active material, a compound capable of reversible intercalation and deintercalation of lithium may be used. Specific examples include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, or Al alloys; and SiO₂ βExamples include metal oxides capable of doping and dedoping lithium, such as (0<β<2), SnO2, vanadium oxide, and lithium vanadium oxide; or composites comprising the metal compound and carbonaceous material, such as Si-C composites or Sn-C composites, and any one or more of these may be used. Additionally, a metallic lithium thin film may be used as the negative electrode active material. Furthermore, the carbon material may include low-crystallinity carbon and high-crystallinity carbon. Representative examples of low-crystallinity carbon include soft carbon and hard carbon, while representative examples of high-crystallinity carbon include amorphous, plate-like, flake-like, spherical, or fibrous natural or artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitch-based carbon fiber, meso-carbon microbeads, mesophase pitches, and high-temperature calcined carbon such as petroleum or coal tar pitch-derived cokes.
[0145] The above-mentioned negative electrode active material may be included in an amount of 80% to 99% by weight relative to the total weight of the negative electrode active material layer.
[0147] The above binder is a component that assists in the bonding between the conductive material, the active material, and the current collector, and can typically be added in an amount of 0.1% to 10% by weight relative to the total weight of the negative active material layer. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethylcellulose (CMC), starch, hydroxypropylcellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber, nitrile-butadiene rubber, fluororubber, and various copolymers thereof.
[0149] The above conductive material is a component for further improving the conductivity of the negative electrode active material, and may be added in an amount of 10% by weight or less, specifically 5% by weight or less, based on the total weight of the negative electrode active material layer. Such conductive material is not particularly limited as long as it is conductive without causing chemical changes in the battery, and for example, graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black; conductive fibers such as carbon fiber or metal fiber; metal powder such as carbon fluoride, aluminum, or nickel powder; conductive whiskers such as zinc oxide or potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives may be used.
[0151] The above-mentioned negative electrode active material layer may be manufactured by applying and drying a composition for forming a negative electrode active material layer, prepared by dissolving or dispersing a negative electrode active material and optionally a binder and a conductive material in a solvent, or by casting the composition for forming a negative electrode active material layer onto a separate support and then laminating the film obtained by peeling from the support onto a negative electrode current collector.
[0153] Meanwhile, in the above-mentioned lithium secondary battery, the separator separates the negative electrode and the positive electrode and provides a pathway for the movement of lithium ions. Any separator typically used in lithium secondary batteries may be used without special limitations, and it is particularly desirable that it has low resistance to the movement of electrolyte ions and excellent electrolyte moisture retention capacity. Specifically, a porous polymer film, such as a porous polymer film made of a polyolefin-based polymer like ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer, and ethylene / methacrylate copolymer, or a laminated structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, such as a nonwoven fabric made of high-melting-point glass fiber or polyethylene terephthalate fiber, may be used. Furthermore, a coated separator containing ceramic components or polymer materials may be used to ensure heat resistance or mechanical strength, and may optionally be used in a single-layer or multi-layer structure.
[0155] In addition, the electrolytes used in the present invention may include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, molten inorganic electrolytes, etc., which are usable when manufacturing lithium secondary batteries, but are not limited to these.
[0156] Specifically, the electrolyte may include an organic solvent and a lithium salt.
[0157] The above organic solvent may be used without special restrictions as long as it can serve as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the above organic solvent may include ester-based solvents such as methyl acetate, ethyl acetate, γ-butyrolactone, and ε-caprolactone; ether-based solvents such as dibutyl ether or tetrahydrofuran; ketone-based solvents such as cyclohexanone; aromatic hydrocarbon-based solvents such as benzene and fluorobenzene; and carbonate-based solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethylmethyl carbonate (EMC), ethylene carbonate (EC), and propylene carbonate (PC). Alcohol-based solvents such as ethyl alcohol and isopropyl alcohol; nitriles such as R-CN (where R is a straight-chain, branched, or cyclic hydrocarbon group having 2 to 20 carbon atoms and may include a double bond-directing ring or ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; or sulfolanes may be used. Among these, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate, etc.) having high ionic conductivity and high dielectric constant that can improve the charge / discharge performance of the battery, and a low-viscosity linear carbonate-based compound (e.g., ethylmethyl carbonate, dimethyl carbonate or diethyl carbonate, etc.) is more preferred.In this case, using a mixture of cyclic carbonate and chain carbonate in a volume ratio of about 1:1 to about 1:9 can result in excellent performance of the electrolyte.
[0159] The above lithium salt can be used without special restrictions as long as it is a compound capable of providing lithium ions used in lithium secondary batteries. Specifically, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The concentration of the lithium salt is preferably used within the range of 0.1 to 5.0 M, specifically 0.1 to 3.0 M. When the concentration of the lithium salt falls within the above range, the electrolyte has appropriate conductivity and viscosity, so it can exhibit excellent electrolyte performance and allow lithium ions to move effectively.
[0161] In addition to the above electrolyte components, the above electrolyte may further include one or more additives for the purpose of improving the lifespan characteristics of the battery, suppressing the decrease in battery capacity, and improving the discharge capacity of the battery, such as, for example, a haloalkylene carbonate-based compound such as difluoroethylene carbonate, pyridine, triethylphosphite, triethanolamine, cyclic ether, ethylene diamine, n-glyme, triamide hexaphosphate, nitrobenzene derivative, sulfur, quinone imine dye, N-substituted oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol, or aluminum trichloride. In this case, the additive may be included in an amount of 0.1 to 10 weight%, specifically 0.1 to 5 weight%, based on the total weight of the electrolyte.
[0163] As described above, since the lithium secondary battery containing the cathode material according to the present invention exhibits excellent lifespan characteristics, resistance characteristics, and capacity characteristics, it is useful in portable devices such as mobile phones, laptop computers, and digital cameras, as well as in the field of electric vehicles such as hybrid electric vehicles (HEVs).
[0164] Accordingly, according to another embodiment of the present invention, a battery module comprising the lithium secondary battery as a unit cell and a battery pack comprising the same are provided.
[0165] The above battery module or battery pack can be used as a power source for one or more medium-to-large devices, including a power tool; an electric vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV); or a power storage system.
[0166] The external shape of the lithium secondary battery of the present invention is not particularly limited, but can be a cylindrical shape using a can, a prismatic shape, a pouch shape, or a coin shape.
[0167] The lithium secondary battery according to the present invention can be used not only as a battery cell used as a power source for a small device, but can also preferably be used as a unit cell in a medium-to-large battery module comprising a plurality of battery cells.
[0169] Hereinafter, embodiments of the present invention are described in detail so that those skilled in the art can easily implement the invention. However, the present invention may be embodied in various different forms and is not limited to the embodiments described herein.
[0171] Examples and Comparative Examples
[0172] Example 1
[0173] Ni 0.605 Co 0.100 Mn 0.295 Complex transition metal hydroxide having a composition represented by (OH)2 (D 50 : 3.8㎛, secondary particle form) and LiOH were added so that the molar ratio of (Ni+Mn+Co):Li was 1:1.05, and Y2O3 was added to Ni 0.605 Co 0.100 Mn 0.295 ZrO2 is prepared such that the Y content is 1,500 ppm relative to the total weight of (OH)2, with Ni 0.605 Co 0.100 Mn 0.295 A mixture was prepared by adding and mixing so that the Zr content was 3,000 ppm relative to the total weight of (OH)2.
[0174] The above mixture was first fired in an oxygen atmosphere to produce a fired product. At this time, the first firing was performed by increasing the temperature from room temperature to 970°C over 5.36 hours, then maintaining the temperature at 970°C for 8.57 hours, and then decreasing the temperature from 970°C to 100°C over 7.5 hours.
[0175] The above sintered product is ground with a jet mill (grinding pressure: 2~4 bar, grinding rate: 50~100 g / min, target D 50 : 3.5~4.0㎛) Next, secondary calcination in an atmospheric environment, Li 1.03 Ni 0.602 Co 0.100 Mn 0.294 Zr 0.003 Y 0.001 A lithium composite transition metal oxide having a composition represented by O2 was prepared. At this time, the secondary calcination was performed by increasing the temperature from 100°C to 955°C for 3.36 hours, then maintaining the temperature at 955°C for 7.09 hours, and then decreasing the temperature from 955°C to room temperature for 2.44 hours.
[0176] The above lithium composite transition metal oxide is ground with a jet mill (Objective D 50: 3.5~4.0㎛) and then, Al2O3 and WO3 were mixed and heat-treated at a temperature of 500℃ for 6 hours under an atmospheric environment to prepare a positive electrode active material comprising a coating portion containing Al and W on the lithium composite transition metal oxide. At this time, the Al2O3 is the Li 1.03 Ni 0.602 Co 0.100 Mn 0.294 Zr 0.003 Y 0.001 Mix so that the aluminum (Al) content is 1,500 ppm relative to the total weight of O2, and WO3 is the above Li 1.03 Ni 0.602 Co 0.100 Mn 0.294 Zr 0.003 Y 0.001 The mixture was prepared such that the content of tungsten (W) was 3,000 ppm relative to the total weight of O2.
[0178] Example 2
[0179] A positive electrode active material was prepared by performing the same procedure as in Example 1 above, except that the second calcination was performed by raising the temperature from 100°C to 960°C instead of 955°C over 3.36 hours, maintaining the temperature at 960°C instead of 955°C for 7.09 hours, and lowering the temperature from 960°C instead of 955°C to room temperature over 2.44 hours.
[0181] Comparative Example 1
[0182] A positive electrode active material was prepared by performing the same procedure as in Example 1 above, except that the second calcination was performed by raising the temperature from 100°C to 950°C instead of 955°C for 3.36 hours, maintaining the temperature at 950°C instead of 955°C for 7.09 hours, and lowering the temperature from 950°C instead of 955°C to room temperature for 2.44 hours.
[0184] Comparative Example 2
[0185] A positive electrode active material was prepared by performing the same as in Example 1 above, except that the second calcination was performed by raising the temperature from 100°C to 965°C instead of 955°C over 3.36 hours, maintaining the temperature at 965°C instead of 955°C for 7.09 hours, and lowering the temperature from 965°C instead of 955°C to room temperature over 2.44 hours.
[0187] Comparative Example 3
[0188] A positive electrode active material was prepared by performing the same procedure as in Example 1 above, except that the first calcination was performed by raising the temperature from room temperature to 980°C instead of 970°C for 5.36 hours, maintaining the temperature at 980°C instead of 970°C for 8.57 hours, lowering the temperature from 980°C instead of 970°C to 100°C for 7.5 hours, and not performing the second calcination.
[0190] Experimental Example
[0191] Experimental Example 1: Particle Analysis 1
[0192] Using an SEM (FEI, Inspect F), SEM images (approx. 5K magnification) of the cathode active materials prepared in the above examples and comparative examples were obtained, and using an image processing program (LG Chem, DX Program), the Dv prepared in the examples and comparative examples A , Dn A , Dv n and the derivative was checked.
[0193] Specifically, SEM images (approx. 5K magnification) of the cathode active materials prepared in the examples and comparative examples were obtained using an SEM (FEI, Inspect F) and are shown in FIGS. 1 to 5. Then, a two-dimensional segmentation image was obtained by dividing the boundaries of the primary particles present in the SEM image using an image processing program (LG Chem, DX Program) and displaying them in random colors. From the segmentation image, the particle size (Dv) of the primary particles corresponding to the arithmetic mean of the volumes of the primary particles was obtained.A The particle size of the primary particle corresponding to the arithmetic mean of ) and the particle size of the primary particle (Dn A Calculate ), and the particle size of the primary particle corresponding to the arithmetic mean of the particle sizes of the primary particles (Dn A The particle size of the primary particle (Dv) corresponding to the arithmetic mean of the volumes of the primary particles for ). A The value (PDI) of ) was calculated, and the results are shown in Table 1 below. In addition, the particle sizes of the primary particles corresponding to 10%, 50%, and 90% of the volumetric cumulative distribution of the primary particles obtained from the SEM images were derived, respectively, and Dv 50, Dv 10 and Dv 90 From span((Dv 90 -Dv 10 ) / Dv 50 ) was calculated, and the results are shown in Table 1 below.
[0194] Meanwhile, regarding fine particles present in the cathode active material, the ratio (%) of the area of fine particles to the total area of primary particles present in the cathode active material—that is, the ratio of the area of primary particles with a particle size of 1 μm or less—was calculated, and the results are shown in Table 1 below. Specifically, the area of the primary particles was measured through the number of pixels corresponding to each of the n primary particles present in the SEM image, and the percentage of the area of fine particles to the total area of the primary particles (fine particle ratio (%)) is shown in Table 1 below.
[0195] The unit uniformity (%) according to Formula 1 described in this specification was calculated from the above PDI, differential ratio, and span, and the results are shown in Table 1 below.
[0197] Figure 1 is an SEM image (approx. 5K magnification) of the cathode active material prepared in Example 1.
[0198] Figure 2 is an SEM image (approx. 5K magnification) of the positive electrode active material prepared in Example 2.
[0199] Figure 3 is an SEM image (approx. 5K magnification) of the cathode active material prepared in Comparative Example 1.
[0200] Figure 4 is an SEM image (approx. 5K magnification) of the cathode active material prepared in Comparative Example 2.
[0201] Figure 5 is an SEM image (approx. 5K magnification) of the cathode active material prepared in Comparative Example 3.
[0203] Through Figures 1 and 2, it was confirmed that the cathode active material prepared in Example 1 and Example 2 comprises a lithium composite transition metal oxide in the form of a single particle consisting of 50 or fewer primary particles.
[0204] In addition, through FIGS. 3 to 5, it was confirmed that the cathode active materials prepared in Comparative Examples 1 to 3 contain a lithium composite transition metal oxide in the form of a single particle composed of 50 or fewer primary particles.
[0206] division PDI span Differential rate (%) Unit uniformity (%) Dn A (㎛) Dv A (㎛) Dv 50 (㎛) Example 1 1.87 0.92 4.1 7.1 1.62 3.02 2.54 Example 2 1.72 0.77 2.9 3.8 1.83 3.14 2.90 Comparative Example 1 1.93 0.93 7.3 13.1 1.38 2.66 3.09 Comparative Example 2 1.82 0.77 2.2 3.1 1.82 3.48 3.42 Comparative Example 3 2.00 0.91 6.5 11.8 1.64 3.28 2.76
[0207] Through Table 1, it was confirmed that the cathode active materials prepared in Examples 1 and 2 have a unit uniformity according to Formula 1 described herein that is 3.8% or higher and 7.5% or lower. Furthermore, the cathode active materials prepared in Examples 1 and 2 have a PDI of 1.50 or higher and 1.90 or lower, and Dn A ga is 1.50 µm or more and 2.00 µm or less, and Dv A ga is 3.00 µm or more and 3.30 µm or less, and Dv 50 It was confirmed that the α is 2.50 μm or more and 3.00 μm or less, and the span is 0.50 or more and 0.95 or less. Meanwhile, it was confirmed that the cathode active materials prepared in Comparative Examples 1 to 3 have a unit uniformity according to Formula 1 described in this specification that is less than 3.5% or greater than 10.0%. Furthermore, the cathode active materials prepared in Comparative Examples 1 and 3 have a PDI greater than 1.90, and the cathode active material prepared in Comparative Example 1 has Dn A The anode active material prepared in Comparative Examples 1 and 2 has a diameter of less than 1.50 μm, and Dv Aa is less than 3.00 µm or greater than 3.30 µm, and Dv 50 It was confirmed that it exceeded 3.00 µm.
[0209] Experimental Example 2: Particle Analysis 2
[0210] For the positive electrode active materials prepared in the above examples and comparative examples, the average particle size (D) of the positive electrode active material using a PSA (Microtrac, S3500) 50 )(㎛) was measured, and the results are shown in Table 2 below.
[0211] division Average particle size (D 50 )(㎛) Example 1 3.83 Example 2 3.81 Comparative Example 1 3.80 Comparative Example 2 3.84 Comparative Example 3 3.83
[0212] Through Table 2, the cathode active materials prepared in Examples 1 and 2 have an average particle size (D) measured by a Particle Size Analyzer (PSA). 50 It was confirmed that ) is 3.00 µm or more and 5.00 µm or less.
[0214] Experimental Example 3: Battery Characteristics Evaluation 1
[0215] Coin-type half-battery manufacturing
[0216] An anode slurry was prepared by mixing 95 wt% of the anode active material prepared in the above examples and comparative examples, 2.0 wt% of carbon black as a conductive material, and 3.0 wt% of polyvinylidene fluoride (PVDF) as a binder in an N-methylpyrrolidone (NMP) solvent. The anode slurry prepared above was applied to one side of an aluminum current collector, dried at 130°C, and then rolled to a porosity of 18% to produce an anode.
[0217] An electrode assembly was manufactured by using a lithium metal electrode as the negative electrode and interposing a porous polyethylene separator between the positive and negative electrodes. This was placed inside a battery case, and a coin-type half-cell was manufactured by injecting an electrolyte solution in which 1.0 M LiPF6 was dissolved in an organic solvent mixed with ethylene carbonate (EC):ethyl methyl carbonate (EMC):diethyl carbonate (DEC) in a volume ratio of 1:2:1.
[0219] Battery Characteristics Evaluation
[0220] After charging to 4.40 V using the CC-CV method (0.1C, cut-off current: 0.05C) at 25℃, the device was discharged to 2.5 V using the CC method (0.1C), and the charge / discharge capacity (mAh / g) was measured. The measured charge / discharge capacity (mAh / g) and the percentage of discharge capacity relative to charge capacity (efficiency (%)) were calculated, and the results are shown in Table 3 below.
[0221] In addition, the initial resistance (Ω) was calculated and is shown in Table 3 below. The above initial resistance value is calculated by dividing the difference between the initial voltage and the voltage at 60 seconds while discharging with a constant current of 0.1 C during the initial charge / discharge by the applied current.
[0222] division Charging capacity (mAh / g) Discharge capacity (mAh / g) Efficiency (%) Initial resistance (Ω) Example 1 217.0 195.5 90.1 25.5 Example 2 217.1 195.3 89.9 25.6 Comparative Example 1 216.5 195.6 90.4 23.5 Comparative Example 2 216.9 194.6 89.7 25.7 Comparative Example 3 216.0 195.6 90.5 22.5
[0223] Through Table 3, it was confirmed that the battery containing the positive active material prepared in Examples 1 and 2 has a charge capacity of 217.0 mAh / g or more. In addition, it was confirmed that the battery containing the positive active material prepared in Example 1, Example 2, Comparative Example 1, and Comparative Example 3 has a discharge capacity of 195.3 mAh / g or more, an efficiency of 89.9% or more, and an initial resistance of 25.6 Ω or less.
[0225] Experimental Example 4: Battery Characteristics Evaluation 2
[0226] Pouch-type monocell battery manufacturing
[0227] An anode slurry was prepared by mixing 95 wt% of the anode active material prepared in the above examples and comparative examples, 2.0 wt% of Super C65 as a conductive material, and 3.0 wt% of polyvinylidene fluoride (PVDF) as a binder in an N-methylpyrrolidone (NMP) solvent. The anode slurry prepared above was coated on one side of an aluminum current collector, dried at 130°C, and then rolled to produce an anode.
[0228] A cathode slurry was prepared by mixing a cathode active material, in which natural graphite and artificial graphite were mixed in a weight ratio of 5:5, a Super C conductive material, an additive (Daicel, DAICEL2200), and a binder (ZEON, BML302) in water in a weight ratio of 95.6:1.0:2.3:1.1. The cathode slurry was applied to one side of a copper current collector, then dried at 130°C and rolled to produce a cathode.
[0229] An electrode assembly was manufactured by interposing a porous polyethylene separator between the positive and negative electrodes. This was placed inside a battery case, and a pouch-type monocell battery was manufactured by injecting an electrolyte solution in which 0.7 M LiPF6 and 0.3 M LiFSI were dissolved in an organic solvent mixed with ethylene carbonate (EC):ethyl methyl carbonate (EMC) in a volume ratio of 3:7.
[0231] Evaluation of battery capacity and lifespan characteristics
[0232] Retention (in-situ) measurement
[0233] The pouch-type monocell manufactured as described above is left at 45°C for 3 hours. After that, charging (0.33C) in the CC-CV method to 4.35V at 45°C and discharging (0.33C) in the CC method to 2.5V is repeated for a total of 200 cycles, and after measuring the discharge capacity in the first cycle and the 200th cycle, the percentage of the discharge capacity of the 200th cycle relative to the discharge capacity of the first cycle (Retention (in-situ) (%)) is shown in Table 4 below.
[0235] Retention (RPT) measurement
[0236] Using the pouch-type monocell manufactured as described above, an initial charge-discharge process is performed by charging (0.33C) in the CC-CV method to 4.35V at 25℃ and then discharging (0.33C) in the CC method to 2.5V, and the initial discharge capacity is measured. After that, a total of 200 cycles of charging and discharging are repeated, with one cycle consisting of charging (0.33C) in the CC-CV method to 4.35V at 45℃ and then discharging (0.33C) in the CC method to 2.5V. After a rest period of 3 hours at 25℃, a subsequent charge-discharge process is performed by charging (0.33C) in the CC-CV method to 4.35V at 25℃ and then discharging (0.33C) in the CC method to 2.5V, and the subsequent discharge capacity is measured. The percentage of the later discharge capacity relative to the initial discharge capacity (Retention (RPT) (%)) is shown in Table 4 below.
[0238] division Retention(in-situ)(%) Retention(RPT)(%) Example 1 93.7 94.7 Example 2 93.8 94.9 Comparative Example 1 93.6 94.4 Comparative Example 2 94.4 95.3 Comparative Example 3 93.4 92.6
[0239] Through Table 4, it was confirmed that the battery containing the positive electrode active material prepared in Example 1, Example 2 and Comparative Example 2 had a retention (in-situ) of 93.7% or higher and a retention (RPT) of 94.7% or higher. In conclusion, it was confirmed that in the case of a battery containing a positive active material having a unit uniformity of 3.5% or more and 10.0% or less according to Formula 1 described in this specification, the charge / discharge capacity, efficiency, and initial resistance characteristics measured in a coin-type half-cell are excellent, while the capacity and life characteristics of the battery measured in a pouch-type monocell are excellent.
Claims
Claim 1 A cathode active material comprising a lithium composite transition metal oxide in a single-particle form consisting of 50 or fewer primary particles, wherein the unit uniformity according to the following Formula 1 is 3.5% or more and 10.0% or less: [Formula 1] Unit uniformity = (PDI × Differential fraction × Span) In the above Formula 1, PDI is Dv A / Dn A and, the differential fraction is the volume percentage [unit: %] of primary particles with a particle size of 1 μm or less among the particle sizes of primary particles obtained from SEM images, and the span is (Dv 90 -Dv 10 ) / Dv 50 and, the above Dv A is the particle diameter of the primary particle [unit: μm] corresponding to the arithmetic mean of the volume of the primary particle obtained from the SEM image, and the above Dn A is the particle size of the primary particle corresponding to the arithmetic mean of the particle sizes of the primary particles obtained from the SEM image [unit: μm], and the above Dv n Is It is the particle size of the primary particle corresponding to n% of the volume cumulative distribution of the primary particle obtained from the SEM image [unit: μm]. Claim 2 A positive electrode active material according to claim 1, wherein the lithium composite transition metal oxide has a nickel (Ni) content of 50 mol% or more among the total metals excluding lithium. Claim 3 A positive electrode active material according to claim 1, wherein the lithium composite transition metal oxide has a composition represented by the following chemical formula 1: [Chemical Formula 1]Li 1+x Ni a Co b Mn c M 1 d In the above chemical formula 1, O2, M 1 ... is one or more selected from the group consisting of Al, Y, Zr, K, Sr, Ba, B, Ce, Cr, Mg, V, Ti, Fe, Zn, Si, Nb, Ga, Sn, Mo, W, and P, and -0.1≤x≤0.3, 0.500≤a<1.000, 0.000 <b<0.500, 0.000<c<0.500, 0.000≤d≤0.100이다. Claim 4 A positive active material according to claim 1, wherein the PDI is 1.50 or higher and 1.90 or lower. Claim 5 In claim 1, the Dn A A positive electrode active material having a thickness of 1.50 μm or more and 2.00 μm or less. Claim 6 In claim 1, the Dv A A positive electrode active material having a thickness of 3.00 μm or more and 3.30 μm or less. Claim 7 In claim 1, the Dv 50 A positive electrode active material having a thickness of 2.50 μm or more and 3.00 μm or less. Claim 8 A positive active material according to claim 1, wherein the span is 0.50 or more and 0.95 or less. Claim 9 A positive active material according to claim 1, wherein the differential fraction is 2.5% or more and 5.0% or less. Claim 10 A positive active material according to claim 1, wherein the unit uniformity is 3.8% or more and 7.5% or less. Claim 11 In claim 1, the average particle size (D) measured by a particle size analyzer (PSA) 50 ) is a positive electrode active material having a thickness of 3.00 μm or more and 5.00 μm or less. Claim 12 A positive electrode comprising a positive electrode active material according to any one of claims 1 to 11. Claim 13 A lithium secondary battery comprising a positive electrode according to claim 12.
